(3GdeUHGMs - (3GdNhGQRej GdeWQRj, CHh GdaJM, HQgGf GdOjf, fGUQ Hf YHO GdSjO CHi GdecGQe, J(B610(3g`s
(3ChdgG (B:s
(3CeG HYO MeO Gddg Pj GdEfYGe hGdUdGI Ydi SjO GdCfGe aEf GdhdO GdCYR GdEeGe CHj HcQ YHO GdbGgQ YHO GdQMef GdLQLGfj aGSJUajJ efgG gPG GdeNJUQ hJQLeJg HcJGH GdeUHGMs
(3BNQgG (B:s
(3hGdaYd GdeXgQ jaSQ dg hEfeG cGf gPG GdfhY dCf GdOGd Ydjg daX CjVG EdG Efg jYbHg heG SHb GdChd GdcdGes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 7 / 348s
(3eYLe GdeDdajf(B: 4 / 9s
(3cTa GdXfhf(B: 2 / 1708s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdfMhs